2000
DOI: 10.1086/317838
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Masses of T Tauri Stars and Calibration of Pre–Main‐Sequence Evolution

Abstract: We have used the high sensitivity and resolution of the IRAM interferometer to produce subarcsecond 12CO J \ 2È1 images of nine protoplanetary disks surrounding T Tauri stars in the Taurus-Auriga cloud (seven singles and two binaries). The images demonstrate the disks are in Keplerian rotation around their central stars. Using the least-square Ðt method described in the 1998 work by Guilloteau & Dutrey, we derive the diskÏs properties, in particular its inclination angle and rotation velocity, hence the dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
482
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 411 publications
(523 citation statements)
references
References 20 publications
35
482
4
Order By: Relevance
“…Although there have been recent advances in determining the masses of 1-2 M pre-main-sequence (PMS) stars, there exist only a few measurements of the masses of sub-solar mass PMS stars (Simon 2001). As a result, theoretical PMS evolutionary tracks have not been well calibrated at the low-mass end, where uncertainties in the models give rise to scatter as large as a factor of 3 in mass and 10 in age (Simon, Dutrey, & Guilloteau 2000). Dynamical measurements of the masses of close binary systems comprised of coeval components with a small mass ratio provide an initial step toward tests of the PMS tracks over a broad parameter range.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been recent advances in determining the masses of 1-2 M pre-main-sequence (PMS) stars, there exist only a few measurements of the masses of sub-solar mass PMS stars (Simon 2001). As a result, theoretical PMS evolutionary tracks have not been well calibrated at the low-mass end, where uncertainties in the models give rise to scatter as large as a factor of 3 in mass and 10 in age (Simon, Dutrey, & Guilloteau 2000). Dynamical measurements of the masses of close binary systems comprised of coeval components with a small mass ratio provide an initial step toward tests of the PMS tracks over a broad parameter range.…”
Section: Introductionmentioning
confidence: 99%
“…By direct imaging, the incredible diversity of the disk morphology, such as spiral and gap structures, has been revealed (e.g., Hashimoto et al 2012). LkCa 15 (K5, 0.97 M⊙, 2−5 Myr old; Simon et al 2000), a young solar-like star located in the Taurus-Auriga region (∼140 pc), is one of the most intensively studied transitional disk systems around the T Tauri star. Espaillat et al (2007) conducted a detailed analysis of SED in LkCa 15 and suggested the existence of a gap structure at ∼46AU.…”
Section: Introductionmentioning
confidence: 99%
“…the competitive accretion ones (Bonnell & Bate 2006), or those proposing Bondi-Hoyle accretion (Keto 2007) predict the existence of a circumstellar accretion disk, in a sort of scaled-up version of low-mass star formation. However, while the existence of Keplerian rotating disks about low-mass young stellar objects (YSOs) and their importance have been assessed well (e.g., Burrows et al 1996;Simon et al 2000), the situation is less clear for higher mass protostars. In several cases, evidence of disks around high-mass YSOs have been reported in the literature (see Beltrán 2011 and references therein).…”
Section: Introductionmentioning
confidence: 99%